2015
DOI: 10.1681/asn.2015040384
|View full text |Cite
|
Sign up to set email alerts
|

The Revisited Classification of GN in SLE at 10 Years

Abstract: Over 10 years have passed since the latest revision of the histopathologic classification of lupus nephritis. This revision was a significant improvement compared with the previous version, mainly because of clearer and more concise definitions and the elimination of mixed subclasses. Despite these improvements, there are still some difficulties in the classification for lupus nephritis, many of which are in the definitions provided. In this review, we focus on the difficulties surrounding the evaluation of cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 44 publications
2
60
0
7
Order By: Relevance
“…Mesangial cell proliferation is among the primary lesion characteristics of LN (27), and the immunofluorescence results suggested that cell proliferation was increased in the biopsied tissue of patients with LN (Fig. 1C).…”
Section: Effect Of Tweak On Nf-κb Transcriptional Activity Hmc Prolimentioning
confidence: 94%
“…Mesangial cell proliferation is among the primary lesion characteristics of LN (27), and the immunofluorescence results suggested that cell proliferation was increased in the biopsied tissue of patients with LN (Fig. 1C).…”
Section: Effect Of Tweak On Nf-κb Transcriptional Activity Hmc Prolimentioning
confidence: 94%
“…In comparison with the older classifications [3,4,18], the ISN/ RPS classification allows a more detailed definition of the different classes with better reproducibility of the results among pathologists [19]. However, there are some points that need to be clarified such as the definition of endocapillary and extracapillary proliferation, a number of glomerular lesions not included in the classification, the value of activity and chronicity index, and the importance of tubulo-interstitial and vascular lesions [20].…”
Section: Introduction To Lupus Nephritismentioning
confidence: 99%
“…At present, data supporting an association between MCD and FSGS with SLE are limited to the observation that these entities seem to be more common in SLE and are often present in the setting of a lupus flare; a goal for the future will be to connect these entities in more than an observational manner. Another important question is whether lupus podocytopathy will be added to the next revision of the classification of LN (7). For now, and in significant part because of the contribution of the work by Hu et al (5), we have reached the point that lupus podocytopathy should be considered a distinct and recognizable disease entity.…”
mentioning
confidence: 99%